Engineering Educators Training in Kazakhstan: Situation and Prospects - Sugralina, L.M.; Minayeva, Ye.V.; Karstina, S.G.; Salkeeva, L.K. (KSU publ., 2019)
The article is a brief overview for the current state of engineering education in Kazakhstan and considers the prospects for its further development and implementation, which is due to the need for industrial and innovative development of our state. Kazakhstan, being an industrially developing country, needs qualified engineering personnel, therefore the training of such specialists at a sufficiently high level is a definite problem. It is noted that for its solution it is necessary to modernize existing study programs, train and retrain teaching staff, widely introduce modern educational approaches and technologies. The article discusses various forms of retraining of teachers of engineering disciplines, for example, advanced training courses for university faculty on the basis of additional education departments. Their topics, duration and forms of conducting are very diverse. Nevertheless, existing problems hinder the development of engineering education in our country; for their successful solution, representatives of the Chemistry and Physics& Technics Departments participate in the international project «EngineeriNg educaTors pEdagogical tRaining» (ENTER). This project implements goals aimed at creating an enabling environment in the educational space based on international cooperation between representatives of universities and the organization of Portugal, Estonia, Slovakia, Russia and Kazakhstan. So, it is planned to elaborate three educational programs (i-PETs) for engineering educators with a variable set of modules based on modern technologies (e-learning) and an individual approach. The implementation of the «ENTER» project is a real prospect of improving the status of engineering education and raising the level of engineering educators’ training in our country.
Keywords: engineering education; engineering educator; study program; advanced training courses